The Information Technology Aided Relapse Prevention Programme in Schizophrenia: an extension of a mirror-design follow-up - Spaniel, F; Vohlídka, P; Kozený, J; Novák, T; Hrdlicka, J; Motlová, L; Cermák, J; Höschl, C (International journal of clinical practice, 2008)
AIMS: Decreasing a number of hospital admissions is important for improving outcomes for people with schizophrenia. The Information Technology Aided Relapse Prevention Programme in Schizophrenia (ITAREPS) programme enables early pharmacological intervention in psychosis by identification of prodromal symptoms of relapse using home telemonitoring via a phone-to-PC SMS platform. METHODS: This study was a 1-year extension of a previously published mirror-design follow-up evaluation of programme clinical effectiveness. In total, 73 patients with psychotic illness (45 patients from original sample and 28 newly added subjects) collaborating with 56 family members participated in the clinical evaluation. RESULTS: There was a statistically significant 77% decrease in the number of hospitalisations during the mean 396.8 +/- 249.4 days of participation in ITAREPS, compared with the same time period before participation in ITAREPS (Wilcoxon-signed ranks test, p < 0.00001), as well as significantly reduced number of hospitalisation days when in the ITAREPS (2365 hospitalisation days before and 991 days after ITAREPS enrolment respectively, Wilcoxon-signed ranks test, p < 0.003). CONCLUSION: The ITAREPS programme represents an effective tool in the long-term treatment of patients with psychotic disorders.
Keywords: hospitalizace; dospělí; Medical Informatics; lékařská informatika; lidé; Female; mužské pohlaví; sekundární prevence; Follow-Up Studies; Male; Schizophrenia; Secondary Prevention; Hospitalization; Adult; následné studie; ženské pohlaví; schizofrenie; Humans